2014
DOI: 10.1016/j.lindif.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Fear appeals used prior to a high-stakes examination: What makes them threatening?

Abstract: Prior to high-stakes examinations teachers use messages that focus on avoiding failure as a motivational strategy. Such messages, referred to as fear appeals, have been linked with negative outcomes. The strength of that link is determined by whether fear appeals are appraised by students as threatening. The aim of this study was to examine whether the threat appraisal of fear appeals was predicted from frequency of message use, academic selfefficacy and subjective values (intrinsic, attainment and extrinsic).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In CVT, discrete emotions (e.g., enjoyment or boredom) arise from differing combinations of control and value appraisals of learning activities or outcomes. Studies have confirmed that relevance is established through attainment value and response options through academic self-efficacy (Putwain & Remedios, 2014a;Putwain, Remedios, & Symes, 2014).…”
Section: Fear Appeals In the Classroommentioning
confidence: 90%
See 4 more Smart Citations
“…In CVT, discrete emotions (e.g., enjoyment or boredom) arise from differing combinations of control and value appraisals of learning activities or outcomes. Studies have confirmed that relevance is established through attainment value and response options through academic self-efficacy (Putwain & Remedios, 2014a;Putwain, Remedios, & Symes, 2014).…”
Section: Fear Appeals In the Classroommentioning
confidence: 90%
“…A challenge appraisal follows high attainment value and high academic self-efficacy whereas a threat appraisal follows high attainment value but low academic self-efficacy (Putwain & Remedios, 2014a;. However, it is not yet known whether challenge and threat appraisal of fear appeals could also influence subsequent attainment value and academic self-efficacy.…”
Section: Is the Appraisal Of Fear Appeals Related To Subsequent Attaimentioning
confidence: 99%
See 3 more Smart Citations